Increased Antimicrobial Activity of Colistin in Combination With Gamithromycin Against Pasteurella multocida in a Neutropenic Murine Lung Infection Model - Li, Yanqin; Xie, Mengjuan; Zhou, Junwen; Lin, Hao; Xiao, Tianan; Wu, Liqin; Ding, Huanzhong; Fang, Binghu (Frontiers in Microbiology, 2020)
We investigated the antimicrobial activity of combined colistin and gamithromycin against nine Pasteurella multocida strains by testing in vitro susceptibility. Two high colistin minimal inhibitory concentration (MIC) isolates (D18 and T5) and one low colistin MIC isolate (WJ11) were used in time-kill tests and therapeutic effect experiments using a neutropenic murine pneumonia model over 24 h. Pharmacokinetics (PK) in plasma was calculated along with pharmacodynamics (PD) to determine the PK/PD index. Synergy between colistin and gamithromycin was observed using high colistin MIC isolates, equating to a 128- or 256-fold and 4- or 8-fold reduction in colistin and gamithromycin concentration, respectively. Interestingly, without synergistic effect on low colistin MIC isolates. However, regardless of the MIC difference among isolates, each drug tended to reach the same concentration in all isolates subjected to combined treatments, which was verified by the time-kill tests presenting similar rates and extent of killing for isolates D18, T5 and WJ11. The AUC (0-24h) / MIC index was used to evaluate the relationship between PK and PD, and the correlation was >0.89. The relevant gamithromycin doses for combined therapy were determined, and the value decreased from 6- to 35-fold compared with monotherapy. Combined colistin and gamithromycin therapy provides a more potent therapeutic regimen than monotherapy against P. multocida strains.